UPAYA KEPALA SEKOLAH MENINGKATKAN KINERJA GURU PADA MASA PANDEMI COVID 19 DI SMK NEGERI 1 TAPEN BONDOWOSO: SMK NEGERI 1 TAPEN BONDOWOSO - ASYIK SULAIMAN (Mitra Pendidikan, 2022)
The aims of the study were 1) To find out the principal's efforts in improving the ability of teachers to plan learning during the COVID-19 pandemi at SMK Negeri 1 Tapen Bondowoso 2). To find out the principal's efforts in improving the ability of teachers to carry out learning during the COVID-19 pandemi at SMK Negeri 1 Tapen Bondowoso 3). To find out the principal's efforts in improving the ability of teachers to evaluate learning during the COVID-19 pandemi The type of research used in this study is a type of qualitative research. This qualitative research is descriptive in the form of speech and writing that can be observed from the subject itself (Arif Furchan. 1992). While the approach used in this research is a case study. Case study research is technically a research conducted intensively, in detail, and in depth on a particular symptom or phenomenon in an organization, institution (Suharsimi Arikunto. 2002). This research was carried out at SMK Negeri 1 Tapen which is located at Jalan Kawah Ijen No. 99 Jurangsapi, Tapen District, Bondowoso Regency for 4 months, from August to November 2021. The data sources of this research are 1) primary data, and 2) secondary data. In qualitative research, data collection is very important in supporting the success of researchers, while the data collection techniques in this study consist of 1) Observation, 2). Interview, 3). Documentation Study The data analysis technique used in this study was carried out by 1). Data reduction, 2). Data presentation, 3). Drawing conclusions. In this study, the principal's efforts to improve teacher performance during the COVID-19 pandemi consisted of 1) improving teacher performance in making lesson plans, 2) improving teacher performance in the learning process, 3) improving teacher performance in learning evaluation.